(3CYeGd GdYeQI hGdRjGQIs - (3Ydi GdehShj GdSHRGhQjs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3aEf ef eff Gddg YR hLd Ydi YHGOg Cf OYGge Edi SHjdg hCQSd Edjge CfHjGAg hQSdg jOYhfge Edi YHGOI Gddg GdhGMO GdCMO hjCeQhfge Edi WGYJg HYOeG HjfhG TQGFYg (B...s
(3BNQgG (B:s
... (3Ke JSLO hJbhd (B: (3Edgj bdHj eMLhH hfaSj eYjhH hYbd eZdhH hghGFj ZGdH hWGYJj bdjd heYUjJj cKjQ hdSGfj ebQ HGdPfhH (B.. (3hUdi Gddg Ydi eMeO hBdgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis